2006
DOI: 10.1021/ac0602470
|View full text |Cite
|
Sign up to set email alerts
|

Ice Chromatography. Characterization of Water−Ice as a Chromatographic Stationary Phase

Abstract: Water-ice has been characterized as a stationary phase for liquid chromatography. Solutes having two or more polar groups are retained on this stationary phase with THF/hexane as the mobile phase, suggesting that multipoint interactions are required for measurable solute retention. Chromatographic separation of phenols or crown ethers on water-ice is possible. The ice surface is expected to provide two different adsorption sites coming from the OH and O dangling bonds. Although the solute partition into the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 34 publications
1
57
0
Order By: Relevance
“…[7][8][9][10] This process can be classified as adsorption. When a salt, for example, is incorporated in the ice stationary phase, the liquid phase emerges as discussed above.…”
Section: Ice Chromatography With Doped Ice As a Stationary Phasementioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] This process can be classified as adsorption. When a salt, for example, is incorporated in the ice stationary phase, the liquid phase emerges as discussed above.…”
Section: Ice Chromatography With Doped Ice As a Stationary Phasementioning
confidence: 99%
“…We first developed ice chromatography, in which ice is used as a chromatographic stationary phase. [7][8][9][10] Various compounds can be separated by this method though there is a limitation in its separation capability. The optical properties of ice are also remarkable; it is transparent over a wide wavelength range, from UV to visible region, and is a rare solid material that has a lower refractive index than do usual liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Ice chromatography, in which ice particles are used as a liquid chromatographic stationary phase, has been used for separation based on adsorption through hydrogen bonding between solutes and the ice surface, [1][2][3] retention control by adsorption/partition switching, 4,5 and chiral separation. 6,7 This method also provides information on phenomena occurring at the interface between the ice and a mobile phase.…”
Section: Introductionmentioning
confidence: 99%
“…We have found that reaction enhancement by freezing depends on the volume of the LP. [3] Ice chromatographic measurements [19] have also revealed that the anomalous enhancement of crown-ether complexation occursw hen the volume of the LP is small, for example, in frozen NaCl of c 0 NaCl < 1mm. [8] The size of the LP was estimatedt ob es omeh undreds of nm for such NaCl concentrations.…”
mentioning
confidence: 99%